Mental health and addiction problems among vulnerable populations and the impact of a supportive text message intervention in one vulnerable group ... - Obuobi-Donkor, Gloria (University of Alberta Library, 2022)
Background Mental health and addiction problems are prevalent among some groups such as the military, firefighters, the elderly, and residents who have experienced multiple disasters. Identifying the prevalence and predictors of mental health and addiction conditions is important for primary prevention and planning treatment programs for these populations. Objectives 1.To identify the prevalence and correlates of post-traumatic stress disorder (PTSD), depressive disorders and suicidality among the military, firefighters, and the elderly. 2. To identify the prevalence and correlates of likely Major Depressive Disorder (MDD), low resilience and, likely cannabis and alcohol abuse in residents of Fort McMurray following the 2016 wildfires, the COVID-19 pandemic and the 2020 flooding. 3. To implement and evaluate the impact of supportive texting service (Text4Hope-Addiction) for subscribers experiencing addiction issues in Alberta, Canada during the COVID-19 pandemic. Methods This thesis includes three separate ...